Organ‐specific symptom patterns during oral food challenge in children with peanut and tree nut allergy. Issue 5 (10th May 2022) - Dobbertin‐Welsch, Josefine; Staudacher, Olga; Yürek, Songül; Trendelenburg, Valérie; Tschirner, Sebastian; Ziegert, Mandy; Ahrens, Frank; Millner‐Uhlemann, Martina; Büsing, Susanne; Striegel, Anne; Ott, Hagen; Arens, Alisa; et al.
Abstract: Background: Peanut and tree nut allergies are common in childhood and often severe in nature. The clinical picture shows a wide variety of symptoms. Objective: To analyze the distribution of clinical symptoms and severity during oral food challenges (OFC) in children. Methods: Analysis of 1.013 prospectively recorded, positive OFCs with peanut ( n  = 607), hazelnut ( n  = 266), walnut ( n  = 97), and cashew ( n  = 43). Symptoms were categorized as immediate‐type skin, gastrointestinal, upper and lower respiratory, cardiovascular symptoms, and eczema exacerbation. Symptom severity and treatment were recorded. Results: Skin symptoms presented in 78%, followed by gastrointestinal (47%), upper (42%), and lower respiratory symptoms (32%). Cardiovascular symptoms presented in 6%. In three‐quarter of the reactions, more than one organ was involved. Importantly, severe reactions occurred at every dose level. Peanut‐ and cashew‐allergic patients had a higher relative risk of gastrointestinal symptoms compared with hazelnut‐ and walnut‐allergic patients. Patients without vomiting had a 1.7 times higher risk developing immediate‐type skin and/or lower respiratory symptoms. Three‐quarter of the patients ever had eczema but worsening presented in only 10.5% of the OFCs. In patients with multiple food allergies, organs involved, eliciting dose and severity differed between allergens. Conclusion: Although comparisons between allergen groups with different clinical history, severity, comorbidities and laboratory data are difficult and might contain bias, our data confirm the high allergenic potential of peanut and tree nuts. The rare occurrence of eczema worsening emphasizes that avoidance diets of peanuts and tree nuts to cure eczema seem to be unnecessary and may hamper tolerance maintenance.